In situ tomographic investigation of damage development in ±45° carbon fibre reinforced laminates. (March 2015) - Sket, F.; Rodríguez-Hortalá, M.; Molina-Aldareguía, J. M.; Llorca, J.; Maire, E.; Requena, G.
<x content-type="archive" xml:space="preserve">Abstract</x> Carbon fibre reinforced epoxy laminates deformed in shear during tensile testing were studied in situ using synchrotron X-ray computed tomography. The deformation and damage mechanisms were evaluated as a function of strain. In particular, the evolution of matrix cracking, interply delamination and fibre rotation was obtained from the tomographies. The investigation provides new insights about the complex interaction between the different damage mechanisms as a function of the applied strain. Quantification of the evolution of the damage mechanisms is presented.